Evaluation of stone columns versus liquefaction phenomenon - Salahi, Arsalan (Hindawi Publishing, 2015)
Liquefaction is a phenomenon which has caused various inherent defects in buildings andstructures in recent years. It is therefore imperative to become familiar with this importantphenomenon in all aspects of Civil Engineering practice and technology. Liquefaction occurs incohesion less soil. Liquefaction is more pronounced during earthquake in which excess porepressure water increases considerably during cyclic loading. In other words, if effective stressbecomes nil during such increase, then Liquefaction is the outcome and in fact, liquefaction occursas sand boil, losing its load bearing capacity. There are many techniques currently available thatcould prevent liquefaction. One such technique is to use stone columns which are the subject ofthis article.